STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS PRODUK LOKALATE DI KALANGAN MAHASISWA UMN - Toni, Ahmad (Fakultas Dharma Duta, 2025)
This research focuses on the marketing communication strategy of Lokalate products in building brand awareness among multimedia Nusantara University students. The method used in this research is a case study related to the P: produk, place, price and promotion. The research results show: Lokalate products aim to present instant coffee product with different flavor variants from their competitors, namely with local (Indonesia) flavors. By Lokalate is by holding a smart campaign as mentioned above, for example on campuses targeting students in campus areas. The promotion that Lokalate chose to do this marketing was due to the high demand for coffee among young people such as college students on the UMN campus.